Identification of Claudin-6 as a Molecular Biomarker in Pan-Cancer Through Multiple Omics Integrative Analysis - Zhang, Chiyuan; Guo, Cuishan; Li, Yan; Liu, Kuiran; Zhao, Qi; Ouyang, Ling (Frontiers in Cell and Developmental Biology, 2021)
Claudin-6 (CLDN6) is one of the 27 family members of claudins and majorly involved in the tight junction and cell-to-cell adhesion of epithelial cell sheets, playing a significant role in cancer initiation and progression. To provide a more systematic and comprehensive dimension of identifying the diverse significance of CLDN6 in a variety of malignant tumors, we explored CLDN6 through multiple omics data integrative analysis, including gene expression level in pan-cancer and comparison of CLDN6 expression in different molecular subtypes and immune subtypes of pan-cancer, targeted protein, biological functions, molecular signatures, diagnostic value, and prognostic value in pan-cancer. Furthermore, we focused on uterine corpus endometrial carcinoma (UCEC) and further investigated CLDN6 from the perspective of the correlations with clinical characteristics, prognosis in different clinical subgroups, co-expression genes, and differentially expressed genes (DEGs), basing on discussing the validation of its established monoclonal antibody by immunohistochemical staining and semi-quantification reported in the previous study. As a result, CLDN6 expression differs significantly not only in most cancers but also in different molecular and immune subtypes of cancers. Besides, high accuracy in predicting cancers and notable correlations with prognosis of certain cancers suggest that CLDN6 might be a potential diagnostic and prognostic biomarker of cancers. Additionally, CLDN6 is identified to be significantly correlated with age, stage, weight, histological type, histologic grade, and menopause status in UCEC. Moreover, CLDN6 high expression can lead to a worse overall survival (OS), disease-specific survival (DSS), and progression-free interval (PFI) in UCEC, especially in different clinical subgroups of UCEC. Taken together, CLDN6 may be a remarkable molecular biomarker for diagnosis and prognosis in pan-cancer and an independent prognostic risk factor of UCEC, presenting to be a promising molecular target for cancer therapy.